2020
DOI: 10.1590/1806-9282.66.s2.130
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence of SARS-CoV-2 vertical transmission: an integrative review

Abstract: SUMMARY OBJECTIVE To review the current scientific evidence of vertical transmission related to coronavirus disease 2019 (COVID-19). METHODS An integrative review was performed by two independent researchers, based on the literature available in the MEDLINE (via PubMed) and LILACS databases, using the descriptors “pregnancy” AND “COVID-19” AND “vertical transmission”. This search included case reports or case series published up until 17th June 2020 in English or Portuguese. After reading the articles avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
10
0
5
Order By: Relevance
“…After studying COVID-19 infection in nine pregnant women, the result suggests that there is no evidence that pregnant women who were infected SARS-CoV-2 in late pregnancy can transmit the virus to infant through intrauterine vertical transmission (Chen N. et al, 2020). However, recently, some studies demonstrated the possibility of vertical transmission of SARS-CoV-2 Deniz and Tezer, 2020;Egloff et al, 2020;Mahyuddin et al, 2020;Oliveira et al, 2020;Parazzini et al, 2020;Peyronnet et al, 2020;Vivanti et al, 2020;. In one case, the newborn whose mother was diagnosed with SARS-CoV-2 in the last trimester was infected with SARS-CoV-2, with neurological compromise.…”
Section: The Epidemiological Characteristics Of Covid-19mentioning
confidence: 99%
“…After studying COVID-19 infection in nine pregnant women, the result suggests that there is no evidence that pregnant women who were infected SARS-CoV-2 in late pregnancy can transmit the virus to infant through intrauterine vertical transmission (Chen N. et al, 2020). However, recently, some studies demonstrated the possibility of vertical transmission of SARS-CoV-2 Deniz and Tezer, 2020;Egloff et al, 2020;Mahyuddin et al, 2020;Oliveira et al, 2020;Parazzini et al, 2020;Peyronnet et al, 2020;Vivanti et al, 2020;. In one case, the newborn whose mother was diagnosed with SARS-CoV-2 in the last trimester was infected with SARS-CoV-2, with neurological compromise.…”
Section: The Epidemiological Characteristics Of Covid-19mentioning
confidence: 99%
“…Some of these negative practices are: 1) women being forced to go through labor and birth without the presence of a partner or support person (34,35), 2) some NICUs not allowing any parental presence at the bedside while others are limiting either the amount of time that the parents can visit or allowing only one parent to be present at a time (36), 3) some hospitals continue to separate mothers who are COVID-19 positive or a Person Under Investigation (PUI) from their infants despite WHO recommendations to avoid this practice (37), 4) discouragement of skin to skin contact and direct breastfeeding (38), 5) early discharge following birth, as early 24 h post-birth for vaginal births and 48 h post-cesarean birth (39, 40), 6) a lack of access to in person pediatric follow-up and hands-on technical breastfeeding assistance (2). Indeed, during the initial phase of the pandemic in Italy, there was concern that breastfeeding had actually been implicated as a "culprit or scapegoat, " despite available evidence suggesting that 1) few pregnant women have been severely affected by COVID-19, 2) evidence for transplacental transmission of the virus very rarely shows a clinical impact, and 3) infected neonates are generally asymptomatic, or have few symptoms, with similar infection rates with vaginal delivery or Cesarean section (41,42).…”
Section: Impact Of the Covid-19 Pandemic On Breastfeeding Mothersmentioning
confidence: 99%
“…Given the extensively documented benefits of human milk and breastfeeding for mothers, infants, the society, and the environment (3,54), as well as the low likelihood of infants becoming ill from COVID-19 (41,42), this is an opportunity for health care professionals to undertake a call to action to protect human milk and breastfeeding. Since no live virus has been detected in human milk whereas specific antibodies against SARS-CoV-2 have (18,23,24), a claim that cannot be attributed to infant formula, health care providers should use the current pandemic to underscore the importance of human milk and breastfeeding as a health promoting and possibly lifesaving medical intervention (55).…”
Section: Call To Action To Protect Human Milk and Breastfeedingmentioning
confidence: 99%
“…Besides the general considerations regarding the drug-to-drug interactions, as the pregnant and the infants are among the most vulnerable groups, and the behavior of the virus among the pregnant women and infants is still ambiguous [3], we aim to review the safety of using the repurposed medications during the pregnancy and breastfeeding in this study. The proposed medications are as mentioned below:…”
Section: Introductionmentioning
confidence: 99%